NEW REGULATORY TELECOM FRAMEWORK: INDIVIDUAL TELECOM DISPUTE RESOLUTION IN INDIA - Mujumdar, Ms. Mugdha; Prabhu, Dr. Sandeep (The journal of contemporary issues in business and government, 2022)
Purpose- To show scrutiny of individual consumer complaint redressal in the Indian telecom regulatory framework. This research gives an understanding of how consumer dispute resolution is structured in India and a different insight to the resolution of grievances of telecom individual consumers, and there is a modification in the framework that may provide satisfactory dispute resolution for individual consumers in the telecom arena. Methodology-Primary analysis of data from 60 respondents using an analytical tool reveals some facts about telecom consumer redressal status in India. A qualitative approach is used for the investigation of primary data. A questionnaire is built to collect primary data. Findings-Analysis says that lack of comprehensible role outline for dispute resolution entity. “Department of Telecom (DoT)” and the “Telecom Regulatory Authority of India (TRAI) “is responsible for ensuring a healthy environment in the telecom sector.It is ambiguity in dispute regulatory roles and the nonexistence of sole authority. “TRAI” should be empowered to take dispute resolution fees from TSP's for the resolution of disputes. The Indian dispute resolution framework shows that India has accepted TSP controlled regulations by setting up the TSP -led consumer redressal process which is not an adequate approach for a satisfactory resolution. However online dispute resolution (ODR) approach is more relevant for consumer dispute resolution which is also a cost- effective and less time-consuming approach. Scope of study-This study will be useful for the researchers, telecom professionals, service providers, policymakers, and think tanks. The originality of work-This research is a comprehensive assessment of TRAI's progress in consumer Redressal.